On the reactivity of Al-group 11 (Cu, Ag, Au) bonds. Issue 10 (16th February 2022) - Liu, Han-Ying; Neale, Samuel E.; Hill, Michael S.; Mahon, Mary F.; McMullin, Claire L.
Abstract : Reactions of the seven-membered cyclic potassium diamidoalumanyl, [KAl(SiN Dipp )]2 (SiN Dipp = CH2 SiMe2 NDipp2 ; Dipp = 2, 6-di-isopropylphenyl), with a variety of Cu(i ), Ag(i ) and Au(i ) chloride N-heterocyclic carbene (NHC) adducts are described. Abstract : Reactions of the seven-membered heterocyclic potassium diamidoalumanyl, [KAl(SiN Dipp )]2 (SiN Dipp = CH2 SiMe2 NDipp2 ; Dipp = 2, 6-di-isopropylphenyl), with a variety of Cu(i ), Ag(i ) and Au(i ) chloride N-heterocyclic carbene (NHC) adducts are described. The resultant group 11-Al bonded derivatives have been characterised in solution by NMR spectroscopy and, in the case of [SiN Dipp Al–Au(NHC iPr )] (NHC iPr = N, N ′-di-isopropyl-4, 5-dimethyl-2-ylidene), by single crystal X-ray diffraction. Although similar reactions of LAgCl and LAuCl, where L is a more basic cyclic alkyl amino carbene (CAAC), generally resulted in reduction of the group 11 cations to the base metals, X-ray analysis of [( Cy CAAC)AgAl(SiN Dipp )] ( Cy CAAC = 2-[2, 6-bis(1-methylethyl)phenyl]-3, 3-dimethyl-2-azaspiro[4.5]dec-1-ylidene) provides the first solid-state authentication of an Ag–Al σ bond. The reactivity of the NHC-supported Cu, Ag and Au alumanyl derivatives was assayed with the isoelectronic unsaturated small molecules, N, N ′-di-isopropylcarbodiimide and CO2 . While these reactions generally provided products consistent with nucleophilic attack of the group 11 atom at the electrophilic heteroallene carbon centre, treatment of the NHC-supported copper and silver alumanyls with N, N ′-di-isopropylcarbodiimide yielded less symmetric Cu– C and Ag– C -bonded isomers. In contrast to the previously described copper and silver alumanyl derivatives, [(NON)Al(O2 C)M(P t -Bu3 )] (M = Cu or Ag; NON = 4, 5-bis(2, 6-di-isopropylanilido)-2, 7-di- tert -butyl-9, 9-dimethylxanthene), which were prone to facile CO extrusion and formation of carbonate derivatives, the NHC-supported dioxocarbene species, [(NHC iPr )M(CO2 )Al(SiN Dipp )] (M = Cu, Ag, Au), are all stable at room and moderately elevated temperatures. The stabilising role of the NHC co-ligand was, thus, assessed by preparation of the t -Bu3 P adducted copper-alumanyl, [( t -Bu3 P)CuAl(SiN Dipp )]. Treatment of this latter compound, which was also structurally characterised by X-ray analysis, with both N, N ′-di-isopropylcarbodiimide and CO2 again provided smooth heteroallene insertion and formation of the relevant Cu– C -bonded products. Although both compounds were quite stable at room temperature, heating of [( t -Bu3 P)Cu(CO2 )Al(SiN Dipp )] at 60 °C induced elimination of CO and formation of the analogous carbonate, [( t -Bu3 P)Cu(OCO2 )Al(SiN Dipp )], which was identified by 13 C and 31 P NMR spectroscopy. Reflective of the more reliable nucleophilic behaviour of the gold centres in these group 11 alumanyls, computational (QTAIM and NBO) analysis highlighted a lower level of covalency of the Al–Au linkage in comparison to the analogous Al–Cu and Al–Ag interactions. Although substitution of the co-ligand significantly perturbs the charge distribution across the Cu–Al bond of [LCuAl(SiN Dipp )] (L = NHC iPr or t -Bu3 P), only a negligible difference is observed between the phosphine-coordinated copper systems derived from either the [SiN Dipp ]- or (NON)-based alumanyl ligands. Computational mapping of the reaction profiles arising from treatment of the various group 11 alumanyls with N, N ′-di-isopropylcarbodiimide indicates that the observed formation of the Cu–N and Ag–N bound isomers do not provide the thermodynamic reaction outcome. In contrast, examination of the CO2 -derived reactions, and their potential toward CO extrusion and subsequent carbonate formation, implies that the identity of the co-ligand exerts a greater influence on this aspect of reactivity than the architecture of the diamidoalumanyl anion.